2021
DOI: 10.1177/2515690x211003727
|View full text |Cite
|
Sign up to set email alerts
|

A Recent Achievement in the Discovery and Development of Vaccines and Therapeutic Agents in the Race for COVID-19 Protection and Treatment

Abstract: Currently, the coronavirus disease 2019 (COVID-19) is a big challenge to the healthcare systems in the world. Several researchers in the world have immediately carried out clinical investigations for the discovery of vaccines and drugs. Different studies have shown that antiviral measures including small bioactive compounds targeting multifaceted molecular communications take in COVID-19 infection. The drug development archived in this review emphasizes mainly on drugs that are effective for the Management of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
1
0
1
Order By: Relevance
“…Moreover, other studies suggested that some NSAID could have antiviral activity in coronaviruses, including SARS-CoV-2 [ 25 ], an activity demonstrated here for ibuprofen. Similarly, tranmadol is an opioid analgesic used to treat moderate to severe pain, that was initially deemed as bad prognosis [ 26 ], but further studies suggested a potential therapeutic effect [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other studies suggested that some NSAID could have antiviral activity in coronaviruses, including SARS-CoV-2 [ 25 ], an activity demonstrated here for ibuprofen. Similarly, tranmadol is an opioid analgesic used to treat moderate to severe pain, that was initially deemed as bad prognosis [ 26 ], but further studies suggested a potential therapeutic effect [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisadores, laboratórios e farmacêuticas trabalharam incessantemente em busca de medicamentos e vacinas eficazes contra a doença que matava, e ainda mata, milhares de pessoas ao redor mundo diariamente (KIFLE et al, 2021;PEIFFER-SMADJA et al, 2021). A primeira dose da vacina contra a COVID-19 foi aplicada no Reino Unido em 08 de dezembro de 2020 (LOPEZ BERNAL et al, 2021).…”
unclassified